Saving God - Masson, Robert (Horizons, 2004)
Thomas Sheehan has made the "atheological" charge that "Christianity's original sin is to think it is about God," but there is a different lesson to take if attention is paid to the metaphoric dimension of the ways Aquinas, Rahner, Heidegger and even Sheehan himself think and speak about God. If there is an original fault from which Christianity must be saved, it has as much to do with the conception of what is happening when Christianity thinks and speaks, as it does with the conception of what this speaking and thinking is about.